Prevalence of sickle cell anemia in Africa: A protocol for a meta-analysis of existing studies - Bwambale Jonani; Emmanuel Charles Kasule; Herman Roman Bwire; Otema Ricky; Joel Fredrick Arturo; Matsiko Livingstone; Nassinde Esther; Namirembe Esther; Namale Joanitah; Lillian Nabbanja Naava; Ssebulime Stephen; John Bosco Mundaka (PLoS ONE, 2025)
Background Sickle cell anemia (SCA) rank 11th among all causes of mortality in Sub-Saharan Africa, with the region accounting for 75% of global cases. Inconsistent diagnostic methods and country-specific data gaps hinder current prevalence estimates. This systematic review and meta-analysis aim to provide pooled prevalence estimates and examine geographic and temporal trends in SCA. Objectives This systematic review and meta-analysis aim to determine the pooled prevalence of SCA across Africa and analyze its geographic and temporal distribution patterns by synthesizing data from existing studies. Methods We will search four major databases: PubMed, Google Scholar, BASE, and Scopus, for studies on SCA prevalence in Africa published between 1994 and 2024. We will use Zotero to remove duplicates and screen titles and abstracts. We will assess the methodological quality with the JBI critical appraisal checklist for studies reporting prevalence data and extract data using a tested MS Excel form from studies with low to moderate bias. We will use random-effects meta-analysis to calculate pooled prevalence estimates and conduct subgroup analyses for heterogeneity. We will evaluate publication bias with funnel plots and Egger’s test, using trim-and-fill analysis if asymmetry is detected. The strength of evidence will be assessed using the AMSTAR (A Measurement Tool to Assess systematic Reviews). Expected Results We expect to find significant variations in SCA prevalence across different regions and age groups, reflecting underlying environmental, diagnostic and methodological factors. We aim to identify any shifts in SCA prevalence and distribution patterns, which could inform future public health strategies and interventions Discussion Our analysis will reveal the pooled prevalence of SCA in Africa, influencing diagnostic, environmental, and methodological factors, guiding targeted public health interventions. Registration Our meta-analysis protocol was registered with the Open Science Framework (OSF) on 8th January, 2025. https://doi.org/10.17605/OSF.IO/M8JXV